2015
DOI: 10.17557/tjfc.50988
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIPS BETWEEN THE SEED YIELD AND SOME AGRONOMIC CHARACTERISTICS OF SAFFLOWER (Carthamus tinctorius L.) UNDER SEMI-ARID CONDITIONS

Abstract: This study was carried out in the experimental field of Faculty of Agriculture, University of Eskişehir Osmangazi, in 2009 and 2010 under semi-arid conditions. Thirteen different safflower cultivars and lines (V-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…(0.466) and biological yield per plot (kg) (0.413). Similar results were found by Roopa and Ravikumar (2008), Shivani et al, (2010), Pavithra (2013) Karimi et al, (2014), Nezhad and Talebi (2015), Sirel and Aytac (2016) and Manjhi (2017).…”
Section: Plant Height (Cm)supporting
confidence: 84%
“…(0.466) and biological yield per plot (kg) (0.413). Similar results were found by Roopa and Ravikumar (2008), Shivani et al, (2010), Pavithra (2013) Karimi et al, (2014), Nezhad and Talebi (2015), Sirel and Aytac (2016) and Manjhi (2017).…”
Section: Plant Height (Cm)supporting
confidence: 84%
“…There is a positive and significant correlation between 1000 seed weight and seed yield. The 1000 seed weight is an important selection criterion that has an indirect effect on improving seed yield in safflower (Arslan, 2007a, b;Camaş & Esendal, 2006;Karimi et al, 2013;Mousavi Ojaq et al, 2020;Sirel & Aytac, 2016). Studies have shown that the 1000 seed weight in safflower varies between 24.7 and 47.8 g (Erbaş et al, 2016), 27.0 and 55.8 g (Arslan & Culpan, 2018), 21.7 and 53.1 g (Ali et al, 2020), 35.2 and 46.9 g (Arslan & Culpan, 2020), 38.0 and 41.0 g (Licata et al, 2023) and shows a wide variation.…”
Section: Seed Weightmentioning
confidence: 99%
“…This gap can be overcome by developing high-yielding cultivars and hybrids, expanding the planted area and increasing seed and oil quality (Debaeke et al, 2021). The number of seeds per head, head diameter and 100-seed weight have a positive and substantial relationship with the yield (Sirel and Aytac, 2016). The primary goal of sunflower breeding is to develop high-yielding hybrids.…”
Section: Introductionmentioning
confidence: 99%